Absence of an N-linked glycosylation motif in the glycoprotein of the live-attenuated Argentine hemorrhagic fever vaccine, Candid #1, results in its improper processing and reduced surface expression - Manning, John T.; Seregin, Alexey V.; Yun, Nadezhda E.; Koma, Takaaki; Huang, Cheng; Barral, Jose; De La Torre, Juan C.; Paessler, Slobodan (Frontiers in Cellular and Infection Microbiology, 2017)
Junin virus (JUNV), a highly pathogenic New World arenavirus, is the causative agent of Argentine hemorrhagic fever (AHF). The live-attenuated Candid #1 (Can) strain currently serves as a vaccine for at-risk populations. We have previously shown that the Can glycoprotein (GPC) gene is the primary gene responsible for attenuation in a guinea pig model of AHF. However, the mechanisms through which the GPC contributes to the attenuation of the Can strain remain unknown. A more complete understanding of the mechanisms underlying the attenuation and immunogenicity of the Can strain will potentially allow for the rational design of additional safe and novel vaccines. Here, we provide a detailed comparison of both RNA and protein expression profiles between both inter- and intra-segment chimeric JUNV recombinant clones expressing combinations of genes from the Can strain and the pathogenic Romero (Rom) strain. The recombinant viruses that express Can GPC, which were shown to be attenuated in guinea pigs, displayed different RNA levels and GPC processing patterns as determined by Northern and Western blot analyses, respectively. Analysis of recombinant viruses containing amino acid substitutions selected at different mouse brain passages during the generation of Can revealed that altered Can GPC processing was primarily due to the T168A substitution within G1, which eliminates an N-linked glycosylation motif. Incorporation of the T168A substitution in the Rom GPC resulted in a Can-like processing pattern of Rom GPC. In addition, JUNV GPCs containing T168A substitution were retained within the endoplasmic reticulum (ER) and displayed significantly lower cell surface expression than wild-type Rom GPC. Interestingly, the reversion A168T in Can GPC significantly increased GPC expression at the cell surface. Our results demonstrate that recombinant JUNV expressing Can GPC display markedly different protein expression and elevated genomic RNA expression when compared to viruses expressing Rom GPC. Additionally, our findings indicate that the N-linked glycosylation motif at amino acid positions 166 to 168 is important for trafficking of JUNV GPC to the cell surface, and the elimination of this motif interferes with the GPC release from the ER.